Assessing Obesogenic School Environments in Sibiu County, Romania: Adapting the ISCOLE School Environment Questionnaire - Mihai Octavian Negrea; Gabriel Octavian Negrea; Gabriela Săndulescu; Bogdan Neamtu; Raluca Maria Costea; Minodora Teodoru; Călin Remus Cipăian; Adelaida Solomon; Mirela Livia Popa; Carmen Daniela Domnariu (MDPI AG, 2023)
The impact of the school environment on childhood weight status has garnered significant attention in recent years. This study aimed to adapt and validate the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE) School and Environment questionnaire in order to assess the potential obesogenic impact of school environments in Sibiu County, Romania. The ISCOLE questionnaire was chosen for its rigorous methodology. It was derived from a comprehensive study conducted across 12 countries which aimed to capture multifaceted influences on childhood weight while emphasizing educational settings in the collection of data. To guide the translation and adaptation of the questionnaire, a multidisciplinary committee was assembled which comprised experts in teaching and school administration to ensure target responder relevance, experts in clinical research to ensure methodological robustness, experts in language adaptation to preserve the original intent of the survey, and experts in public health to steer the interpretation of the results, with potential policy implications. The data were analyzed by distinguishing between urban and rural settings, and a two-step cluster analysis was implemented to identify potential intervention targets. To assess the validity of the adapted tool, the questionnaire's construct validity and internal consistency were explored. A response rate of 71.2% of the approached schools in Sibiu County was achieved. Of the 84 responding school representatives, 37 (44%) were from a rural setting. The rural schools had significantly more limited access to gymnasiums, secured lockers, showers, and bicycle racks, and exhibited more serious problems regarding the inadequate disposal of garbage in the school vicinity. A two-step cluster analysis revealed distinct school categories, providing opportunities for public policy interventions. One of these primarily concerned rural schools with limited infrastructure but with proactive practices and policies which were termed "unable but willing"; on the opposing spectrum, the category "able but unwilling" mainly comprised urban schools which had available facilities but lacked local proactive initiatives. The findings emphasize the urgent need for targeted measures to bridge these discrepancies by investing in infrastructure in rural schools and promoting active school practices and policies in urban settings. The assessment of obesogenic school environments in Sibiu County provides a pilot model for broader applications due to the diverse school landscape and supportive local authorities. The results, which were achieved using low-cost methods, can guide future educational policies, health promotion initiatives, and preventive interventions.